A conserved role of the duplicated Masculinizer gene in sex determination of the Mediterranean flour moth, Ephestia kuehniella - Visser, Sander; Voleníková, Anna; Nguyen, Petr; Verhulst, Eveline C; Marec, František (PLoS genetics, 2021)
Sex determination in the silkworm, Bombyx mori, is based on Feminizer (Fem), a W-linked Fem piRNA that triggers female development in WZ individuals, and the Z-linked Masculinizer (Masc), which initiates male development and dosage compensation in ZZ individuals. While Fem piRNA is missing in a close relative of B. mori, Masc determines sex in several representatives of distant lepidopteran lineages. We studied the molecular mechanisms of sex determination in the Mediterranean flour moth, Ephestia kuehniella (Pyralidae). We identified an E. kuehniella Masc ortholog, EkMasc, and its paralog resulting from a recent duplication, EkMascB. Both genes are located on the Z chromosome and encode a similar Masc protein that contains two conserved domains but has lost the conserved double zinc finger domain. We developed PCR-based genetic sexing and demonstrated a peak in the expression of EkMasc and EkMascB genes only in early male embryos. Simultaneous knock-down experiments of both EkMasc and EkMascB using RNAi during early embryogenesis led to a shift from male- to female-specific splicing of the E. kuehniella doublesex gene (Ekdsx), their downstream effector, in ZZ embryos and resulted in a strong female-biased sex-ratio. Our results thus confirmed the conserved role of EkMasc and/or EkMascB in masculinization. We suggest that the C-terminal proline-rich domain, we have identified in all functionally confirmed Masc proteins, in conjunction with the masculinizing domain, is important for transcriptional regulation of sex determination in Lepidoptera. The function of the Masc double zinc finger domain is still unknown, but appears to have been lost in E. kuehniella.
Keywords: duplikace genu; Sex Chromosomes; Male; pohlavní chromozomy; vývojová regulace genové exprese; můry; Sex Determination Processes; Gene Expression Regulation, Developmental; Organ Specificity; hmyzí proteiny; mužské pohlaví; stanovení celkové genové exprese; Gene Duplication; Gene Expression Profiling; proteinové domény; Animals; alternativní sestřih; ženské pohlaví; zvířata; Insect Proteins; Alternative Splicing; procesy určující pohlaví; Female; Protein Domains; orgánová specificita; Dosage Compensation, Genetic; kompenzace dávky (genetika); Moths